SKALA TINGKAT NYERI PENDERITA CERVICAL ROOT SYNDROME (CRS) PADA PENJAHIT SASIRANGAN: Pain Level Scale For Cervical Root Syndrome (CRS) Patients In Sasirangan Tailors - Dian Intan Permatasari (Jurnal Kajian Ilmiah Kesehatan dan Teknologi, 2024)
Sasirangan cloth tailors are required to work in the same posture with a long duration so they are prone to feel cervical root syndrome pain that also can hinder their productivity. This study aims to describe the tailor’s pain level of cervical root syndrome on Sasirangan. This research conducted in Sasirangan with descriptive-analitical design, purposive sampling technique and using the Visual Analog Scale (VAS) as a measuring instrument. The result showed that the majority of respondents are belonged to early adult age group with range 21-40 years old about 16 respondents (48,5%), women about 26 respondents (78,8%), have working experience ≥ 10 years about 20 respondents (60,6%), felt a mild level pain when standing still about 27 respondents (81,8%), mild level pain when flexing about 24 respondents (72,7%), moderate level pain when doing lateral flexy sinistra about 16 respondents (48,5%) dan rotation sinistra about 17 respondents (51,5%); and moderate tenderness pain about 14 respondents (42,4%) on C6 area about 17 respondents (51,5%).